Ipr1 gene mediates innate immunity to tuberculosis (2005)
ABSTRACT: An estimated 8 million people are infected each year with the pathogen, Mycobacterium tuberculosis, and over 2 million die annually1. Yet only about 10% of those infected develop tuberculosis. Genetic variation within host populations is known to play a significant role in humans and animals 2,3, but the nature of genetic control of host resistance to tuberculosis remains poorly understood. Previously we mapped a new genetic locus on mouse chromosome 1, designated sst1 (for supersusceptibility to tuberculosis1)4. Here we demonstrate in sst1 congenic mouse strains that this locus mediates innate immunity, and identify a candidate gene, Intracellular Pathogen Resistance 1 (Ipr1), within the sst1 locus. The Ipr1 gene is upregulated in the sst1 resistant macrophages upon activation and infection, but is not expressed in the sst1 susceptible macrophages. Expression of the Ipr1 transgene in the sst1 susceptible macrophages limits multiplication not only of MTB but also Listeria monocytogenes and switches a cell death pathway of the infected macrophages from necrosis to apoptosis. Our data suggest that the Ipr1 gene product may play a novel role in integrating signals generated by intracellular pathogens with mechanisms controlling innate immunity, cell death and pathogenesis.